Identifying characteristic signatures between soil moisture and heterotrophic soil respiration - Widanagamage, Lasanthika Nishadini (Kansas State University, 2024)
Heterotrophic soil respiration is the release of carbon dioxide (CO₂) from the soil that originates from the microbial decomposition of soil organic matter. Recognizing how this process responds to management and environmental factors is crucial for predicting changes in soil carbon levels and assessing the potential impact of climate change on terrestrial carbon stocks. This dissertation delves into the connection between heterotrophic soil respiration, soil temperature, soil moisture, and land cover using a series of laboratory and field experiments. The first chapter of this research explores the relationship between heterotrophic soil respiration and soil water potential using undisturbed soil samples collected from three different, but adjacent, land covers with the same soil textural class. The study investigates the impact of land cover in heterotrophic soil respiration and emphasizes the role of soil water potential in regulating the dynamics of this process. The second part of the study examines the link between heterotrophic soil respiration, soil temperature, and soil moisture by combining in situ measurements of soil CO₂ emissions with in situ soil water retention curves. Using asset of instrumented collars, this chapter describes an innovative alternative to measuring collocated soil matric potential, soil temperature, volumetric water content, and heterotrophic soil respiration. Our findings show the importance of conducting in situ measurements, particularly in well-aggregated soils, to improve the soil respiration–soil moisture relationship used by mechanistic models to better forecast terrestrial carbon stocks under different climate change scenarios.
Keywords: Soil respiration; Soil water potential; Water-filled porosity; In situ soil water retention curves